The Effect of Service Quality and Customer Perceived Value The Intention To Do A Medical Check-Up With Patient Satisfaction as A Mediating Variable at Medika BSD Hospital - Hartining Utami, Isnugraika; Yanuar Rahmat Syah, Tantri; Rokiah, Rokiah (Devotion : Journal of Research and Community Service, 2024)
The intention to do MCU is a behavior after the patient has evaluated the quality of service, customer value, and patient satisfaction offered by health facilities. Low intention to perform MCU leads to a decrease in the number of patient visits in MCU units and leads to hospital losses. Data shows that the number of MCU patient visits in 2022 has decreased by 29.35% compared to 2021. Objective: To analyze the influence of service quality and customer perceived value on the intention to do MCU mediated by patient satisfaction. Methods: This study is a quantitative research and data collection using questionnaires. The number of samples was 135 respondents. This study uses the SEM method with the LISREL application for data analysis and SPSS for validity and reliability pretest tests. Results: Service quality has a positive and significant effect on customer perceived value. Service quality and customer perceived value have a positive and significant effect on patient satisfaction. Service quality, customer perceived value, and patient satisfaction have a positive and significant effect on the intention to do MCU. Service quality and customer perceived value have a positive and significant effect on the intention to do MCU mediated by patient satisfaction. Implications: This study has positive implications in helping hospital quality evaluation and marketing with the active role of the quality management system and hospital marketing system. Suggestion: The importance of socializing, monitoring and evaluating SOPs and MCU service flows. It is necessary to evaluate MCU patient satisfaction periodically to get an overview of service quality, and an active role of marketing is needed to carry out marketing strategies with the implementation of 7Ps, especially price, promotion, and process.